Flame Retarded Rigid Polyurethane Foams Composites Modified by Aluminum Diethylphosphinate and Expanded Graphite - Hu, Yuxiang; Zhou, Zijian; Li, Shuisheng; Yang, Dong; Zhang, Shui; Hou, Yakang (Frontiers in Materials, 2021)
Rigid polyurethane foam (RPUF) was an organic porous material, which was applied in many fields for excellent thermal insulation and mechanical properties, especially in building insulation. However, the poor fire performance significantly suppresses its further application. In this work, aluminum diethylphosphinate (ADP) combined with expanded graphite (EG) to form a synergistic flame retarded system, which was introduced to fabricate flame retarded rigid polyurethane foam composites (FR-RPUF) by one-step water-blown method. Furthermore, thermal insulation, thermal stability, fire performance as well as decomposition products of RPUF and FR-RPUF composites were systematically investigated. It was found that FR-RPUF composites possessed LOI of 25.9 vol% with V-1 rating in UL-94 test when 10 php of ADP and 20 php of EG were added, which were better than RPUF composites with ADP or EG added alone. MCC test showed that RPUF/ADP24/EG6 had the lowest PHRR value of 159.85 W/g, which was 52.01 W/g lower than that of pure RPUF. Gas phase products investigation implied that the combination of ADP and EG could decrease toxic and combustible gases intensities, thus significantly enhance fire safety of FR-RPUF composites. SEM test indicated that ADP and EG promoted the formation of dense and continuous char residue, which significantly inhibited heat and substance transfer in combustion, thus significantly enhance fire performance of FR-RPUF composites.